Optimalisasi Peran Pendidikan Pancasila dalam Menumbuhkan Sikap Toleransi dan Kepedulian Sosial di Kalangan Mahasiswa - Ari Metalin Ika Puspita; Aprilia Early Al Ghony; Merida Rahma Paramita; Najwa Meisya Albahri; Mutiara Nora Ayu; Gladistha Putri Dwi Gumilar (International Forum of Researchers and Lecturers, 2024)
This article discusses the importance of Pancasila education in shaping tolerance and social awareness among Indonesian university students. Based on the nation's five core principles, Pancasila education plays a crucial role in developing the character of the younger generation. By instilling strong moral and ethical values, this education aims to equip students with the ability to face social challenges wisely and responsibly. This study employs a qualitative method with a descriptive-analytical approach through library research. The findings indicate that Pancasila education can create a conducive learning environment for students' self-development, encompassing not only intellectual aspects but also the formation of moral character. The implementation of this education includes interactive teaching methods, practical experiences, and character education development. Effective methods include group discussions, case studies, community service programs, and student organization activities. In conclusion, Pancasila education must be an integral part of the higher education curriculum to ensure that students thoroughly understand and apply Pancasila values in their daily lives. This is expected to produce a young generation with strong character, tolerance, and social awareness, contributing to the formation of a harmonious and just society.